2018
DOI: 10.1016/j.carbon.2017.12.058
|View full text |Cite
|
Sign up to set email alerts
|

High-yield single-step catalytic growth of graphene nanostripes by plasma enhanced chemical vapor deposition

Abstract: a b s t r a c tWe report a single-step growth process of graphene nanostripes (GNSPs) by adding certain substituted aromatics (e.g., 1,2-dichlorobenzene) as precursors during the plasma enhanced chemical vapor deposition (PECVD). Without any active heating and by using low plasma power ( 60 W), we are able to grow GNSPs vertically with high yields up to (13 ± 4) g/m 2 in 20 min. These GNSPs exhibit high aspect ratios (from 10:1 to >~130:1) and typical widths from tens to hundreds of nanometers on various trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…Exemplifying Raman spectra for PECVD-grown monolayer graphene sheet and GNSPs are shown in Figure 2.1(a) and Figure 3.1(g), respectively. Generally the Raman spectra of pristine graphene monolayer do not include the D-band, whereas the Raman spectra of GNSPs and of all VG-GNs always include a D-band due to many exposed edges in the nanostructures [61,173]. We further note that the ratio of the 2D-band to G-band, (I 2D /I G ), is an important identifier of graphene quality.…”
Section: Characterizationmentioning
confidence: 88%
See 4 more Smart Citations
“…Exemplifying Raman spectra for PECVD-grown monolayer graphene sheet and GNSPs are shown in Figure 2.1(a) and Figure 3.1(g), respectively. Generally the Raman spectra of pristine graphene monolayer do not include the D-band, whereas the Raman spectra of GNSPs and of all VG-GNs always include a D-band due to many exposed edges in the nanostructures [61,173]. We further note that the ratio of the 2D-band to G-band, (I 2D /I G ), is an important identifier of graphene quality.…”
Section: Characterizationmentioning
confidence: 88%
“…In the latter case the resulting nanostructures were mostly "wall-like" with typical length-to-width aspect ratios <~ 10, whereas the growth rate may be increased with increasing plasma power [10]. Additionally, we found that DCB precursors further enhanced the presence of C 2 radicals (Figure 3.2(c)), which also contributed to the high-yield growth of GNSPs [61]. Hydrophobicity/hydrophilicity is generally an important characteristic of nanomaterials.…”
Section: Vg-gn Materials Characteristicsmentioning
confidence: 88%
See 3 more Smart Citations